2019
DOI: 10.3389/fmicb.2019.02863
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Resolution of Functional Diversity in Copper Surface-Associated Marine Biofilms

Abstract: We used metagenomic sequencing combined with morphological and chemical analyses to investigate microbial taxa and functions related to copper-resistance and microbiologically influenced corrosion in mature copper-associated biofilms in coastal seawater for 44 months. Facultative anaerobic microbes such as Woeseia sp. were found to be the dominant groups on the copper surface. Genes related to stress response and possible heavy metal transport systems, especially RNA polymerase sigma factors (rpoE) and putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…For metagenomic sequencing of total DNA, the construction of sequencing libraries and the determination of the size distribution and concentration of purified products in libraries were performed according to Zhang et al 65 . The sequencing of prepared libraries was performed on the Illumina HiSeq PE250 platform after generating clustered index-coded samples.…”
Section: Discussionmentioning
confidence: 99%
“…For metagenomic sequencing of total DNA, the construction of sequencing libraries and the determination of the size distribution and concentration of purified products in libraries were performed according to Zhang et al 65 . The sequencing of prepared libraries was performed on the Illumina HiSeq PE250 platform after generating clustered index-coded samples.…”
Section: Discussionmentioning
confidence: 99%
“…Sva1033 metabolism has been associated with metal reduction ( Sun et al, 2013 ; Buongiorno et al, 2019 ). Woeseia was the most abundant genus in a copper biofilm ( Zhang et al, 2019 ) and metagenomic data suggested a broad range of metabolism for Woeseiaceae , including sulfur-based chemolithoautotrophy ( Mußmann et al, 2017 ). OPB41 refers to a 16S rRNA gene amplicon sequence detected for the first time in a Yellowstone hot spring, an environment with high concentrations of reduced iron and sulfur ( Hugenholtz et al, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al analysed the in situ microbial diversity in artificial surface-associated marine biofilms and found that EPS-related genes were more abundant in copper-associated biofilms than that in aluminium-associated biofilms. They thus proposed that copper corrosion in natural marine environments was attributed to the heterogeneous microenvironments within the biofilms caused by the EPS [ 120 ]. Fang et al found that EPS increased the corrosion of mild steel due to its acidity and its binding with iron [ 121 ].…”
Section: Eps and Biocorrosionmentioning
confidence: 99%